Faktor-Faktor Yang Berhubungan Dengan Kinerja Perawat Di Rumah Sakit PKU Muhammadiyah Yogyakarta Unit 2 - Diah Cahya Lestari; Ahmad Ahid Mudayana (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2015)
Background : Nurses are profesionals who have the ability, responsinility and avthority to implement and provide care for patiens who experienced health problems. Nurses was closely linked to the performance because the performance is the result or the overall success rate of a person during a certain period in the duty compared to the various possibilities, such as the standard of the work, the target or criteria that have been determined in advance and has agreed.Method: This was an analytic research use cross sectional approach conducted on as many as 103 nurses using a questionnaire research. Instruments by using chi square analysis.Result : There was a significant relationship between compensation (p value= 0,001;CI = 1,358-3,989) and job satisfaction (p value = 0,019; CI = 1,132-2,831) with the performance of the nurses and there is a significant relationship between organizational behavior (p value = 0,003; CI = 1,295-3,358) and leadership (p value =0,001; CI = 1,433-4,968) with the nurses performance.Conclusion : There was a relationship between compensation, job satisfaction, organizational behavior, leadership with nurses performance.